Does the Duration of Perioperative Antibiotic Prophylaxis Influence the Incidence of Postoperative Surgical-Site Infections in Implant-Based Breast Reconstruction in Women with Breast Cancer? A Retrospective Study. Issue 4 (31st January 2022) - Rothe, Kathrin; Münster, Nathalie; Hapfelmeier, Alexander; Ihbe-Heffinger, Angela; Paepke, Stefan; Niemeyer, Markus; Feihl, Susanne; Busch, Dirk H.; Kiechle, Marion; Brambs, Christine E.
Abstract : Background: Perioperative antibiotic prophylaxis is an established concept to reduce the risk of surgical-site infections; however, the optimal treatment duration in prosthetic breast reconstruction is still controversial. This study evaluated a potential association between the perioperative antibiotic prophylaxis duration (≤24 hours versus >24 hours) and incidence of postoperative surgical-site infections in immediate implant-based breast reconstruction in breast cancer patients. Methods: A descriptive, retrospective analysis of surgical-site infections after immediate implant-based breast reconstruction in breast cancer patients between January of 2011 and December of 2018 was performed. The incidence of postoperative surgical-site infections in patients with more than 24 hours of perioperative antibiotic prophylaxis was compared to patients treated for 24 hours or less. Results: A total of 240 patients who met criteria were included. There were no relevant epidemiologic, clinical, or histopathologic differences between groups. Surgical-site infections as defined by the Centers for Disease Control and Prevention criteria occurred in 25.8 percent. A risk factor–adjusted analysis by a prespecified multiple logistic regression model showed that 24 hours or less of perioperative antibiotic prophylaxis was not inferior to treatment for more than 24 hours. The upper limit of the one-sided 95 percent confidence interval of the risk difference was 9.4 percent (below the prespecified noninferiority margin of 10 percent leading to statistical significance). Risk factors for a surgical-site infection included obesity and postoperative wound complications. Conclusions: The study found no association between short-course perioperative antibiotic prophylaxis (≤24 hours) and an increased rate of postoperative surgical-site infection. This is of high clinical relevance because short-course treatment can help reduce side effects and the emergence of antimicrobial resistance and prevent surgical-site infections as effectively as a prolonged perioperative antibiotic prophylaxis course. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.